Report on Candidates' Work in the Secondary Education Certificate Examination June 2007: Typewriting - Caribbean Examinations Council (CXC, 2007)
This report contains general and detailed comments on the performance of candidates in the June 2007 Caribbean Secondary Education Certificate Examination (CSEC) in Typewriting at the General Proficiency level.
Keywords: CXC CSEC examinations